Detection of Southern Rice Black-Streaked Dwarf Virus Using Western Blotting With P6 - Xie, Xin; Jiang, Junmei; Huang, Maoxi; Chen, Meiqing; Qu, Zhiguang; Li, Xiangyang (Frontiers in Sustainable Food Systems, 2021)
The southern rice black-streaked dwarf virus (SRBSDV) is a severe threat to the yield and quality of rice products worldwide. Traditional detection methods for diagnosing SRBSDV infection show several false positives and thus provide inaccurate findings. However, Western blotting (WB) can precisely solve this problem. In this study, P6—a viral RNA-silencing suppressor—was expressed and purified in vitro. Two polyclonal P6 antibodies were obtained and quantified by enzyme-linked immunosorbent assay and WB. Subsequently, WB was performed using the P6 antibodies to identify SRBSDV antigens derived from the suspected rice samples collected from nine districts in Guizhou, China. The assay results showed that Libo, Pingtang, Huishui, Dushan, and Anshun districts had experienced an SRBSDV outbreak. The virus content in the sampled rice tissues was quantified by WB. Our results revealed that SRBSDV mainly accumulated in rice stems rather than rice leaves. Thus, the findings of our study show that the SRBSDV P6 antibody can be used in WB for detecting and monitoring SRBSDV infection in infected rice plants.